In Vitro Effect of Sodium Fluoride on Malondialdehyde Concentration and on Superoxide Dismutase, Catalase, and Glutathione Peroxidase in Human Erythrocytes - José Gutiérrez-Salinas; Liliana García-Ortíz; José A. Morales González; Sergio Hernández-Rodríguez; Sotero Ramírez-García; Norma R. Núñez-Ramos; Eduardo Madrigal-Santillán (The Scientific World Journal)
The aim of this paper was to describe the in vitro effect of sodium fluoride (NaF) on the specific activity of the major erythrocyte antioxidant enzymes, as well as on the membrane malondialdehyde concentration, as indicators of oxidative stress. For this purpose, human erythrocytes were incubated with NaF (0, 7, 28, 56, and 100 μg/mL) or NaF (100 μg/mL) + vitamin E (1, 2.5, 5 and 10 μg/mL). The malondialdehyde (MDA) concentration on the surface of the erythrocytes was determined, as were the enzymatic activities of superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GlPx). Our results demonstrated that erythrocytes incubated with increasing NaF concentrations had an increased MDA concentration, along with decreased activity of antioxidant enzymes. The presence of vitamin E partially reversed the toxic effects of NaF on erythrocytes. These findings suggest that NaF induces oxidative stress in erythrocytes in vitro, and this stress is partially reversed by the presence of vitamin E.